Quizizz as a Gamification Tool for Enhancing Digital Arabic Literacy and Learning Outcomes among Students - Alif Laela (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
The rapid evolution of information technology has transformed the pedagogical landscape, yet many madrasahs still rely on conventional instructional methods, leading to low student engagement and suboptimal digital Arabic literacy. This study evaluates the effectiveness of Quizizz as a gamified learning platform in enhancing digital Arabic literacy and learning outcomes. Utilizing a quantitative approach with a quasi-experimental non-equivalent control group design, the research involved 62 eighth-grade students at MTsN 6 Tulungagung, consisting of 30 students in the experimental group (8J) and 32 in the control group (8H). Data were gathered through pre-tests, post-tests, and a digital literacy questionnaire, subsequently analyzed using SPSS 20. The findings indicate a significant improvement in the experimental group's learning outcomes, with mean scores rising from 59.53 to 78.13. The N-gain score of 0.46 reflects moderate effectiveness, while a Cohen’s d of 2.44 signifies a very large effect size. Furthermore, simple linear regression reveals that Quizizz accounts for 59.9% of the variance in digital Arabic literacy (R2 = 0.599), with a significant regression coefficient (B = 0.862, p < 0.05). These results suggest that integrating interactive gamified media fosters a more engaging and learning environment, effectively bridging the gap between traditional Arabic linguistics and modern technological proficiency.